The Wolff- Parkinson-White and related syndromes : an electrocardiographic appraisal - Krikler, Dennis Michael (Department of Medicine, 2020)
This is an electrocardiological study, based on electrocardiographic analysis of new cases as well as on a review of some features, hitherto unrecognized or not stressed, in subjects with these disorders, that may help throw more light on them. In six cases studied personally using intracardiac electrography - the technique of His bundle electrography - the contribution and relevance of this method will be analysed, and the results compared with the conclusions drawn from other contemporary work in this field. Thus, the clinical presentation of the cases, and of these syndromes, receives secondary attention, and more detailed analysis only when appropriate to substantiate the main burdens of the thesis. These case reports appear separately in Section c. The mechanism of production of arrhythmias is becoming much better understood, and some of the diagnostic measures that are discussed in this work provide a clearer picture of their genesis. It is not proposed to embark upon a detailed consideration of anti-arrhythmic therapy in these syndromes, but the general principles will be discussed, and special reference will also be made to some new developments in this field.